Occurrence and epidemiology of fruit rot of guava caused by Phytophthora nicotianae var. parasitica - and KUSUM MATHUR, SNEH MATHUR, M.K. BHATNAGAR (Indian Phytopathology, 2012)
In addition to fruits, guava Phytophthora also infects leaves and young twigs. Favourable weather conditions in ensuing season significantly increase the disease intensity and fruit rot in orchards with infected trees. The disease is favoured by high humid conditions (RH above